Phenotypic Robustness of Epidermal Stem Cell Number in C. elegans Is Modulated by the Activity of the Conserved N-acetyltransferase nath-10/NAT10 - Hintze, Mark; Katsanos, Dimitris; Shahrezaei, Vahid; Barkoulas, Michalis (Frontiers in Cell and Developmental Biology, 2021)
Individual cells and organisms experience perturbations from internal and external sources, yet manage to buffer these to produce consistent phenotypes, a property known as robustness. While phenotypic robustness has often been examined in unicellular organisms, it has not been sufficiently studied in multicellular animals. Here, we investigate phenotypic robustness in Caenorhabditis elegans seam cells. Seam cells are stem cell-like epithelial cells along the lateral edges of the animal, which go through asymmetric and symmetric divisions contributing cells to the hypodermis and neurons, while replenishing the stem cell reservoir. The terminal number of seam cells is almost invariant in the wild-type population, allowing the investigation of how developmental precision is achieved. We report here that a loss-of-function mutation in the highly conserved N-acetyltransferase nath-10/NAT10 increases seam cell number variance in the isogenic population. RNA-seq analysis revealed increased levels of mRNA transcript variability in nath-10 mutant populations, which may have an impact on the phenotypic variability observed. Furthermore, we found disruption of Wnt signalling upon perturbing nath-10 function, as evidenced by changes in POP-1/TCF nuclear distribution and ectopic activation of its GATA transcription factor target egl-18. These results highlight that NATH-10/NAT-10 can influence phenotypic variability partly through modulation of the Wnt signalling pathway.